Blue toe syndrome: a rare presentation of atrial myxoma - Ab. Rahman, Norhafiza; Othman, Ahmad Faidzal; Awang, Ahmad Khadri (2014)
Blue toe syndrome is a condition in which patient presented with cyanotic toe caused by fibrino-platelet micro-emboli occlusion of the small digital arteries while atrial myxoma is the most common primary cardiac tumour. Most patients with atrial myxoma present with emboli to blood vessel of the brain causing ischaemic stroke. We report a case of a 37 year old gentleman who presented with blue toe syndrome affecting right second and fourth toes without any symptoms and signs of cardiac insufficiency or other embolus elsewhere. Further investigation and echocardiography revealed a mass over the left atrium that lead to the provisional diagnosis of atrial myxoma. He underwent excision of the left atrial myxoma with repair of interatrial septum within the same admission. Surgery was uneventful and he was discharged home well.